2010
DOI: 10.3749/canmin.48.5.1137
|View full text |Cite
|
Sign up to set email alerts
|

SYNTHETIC CUBANITE CuFe2S3: PRESSURE-INDUCED TRANSFORMATION TO ISOCUBANITE

Abstract: Cubanite, the orthorhombic polymorph of CuFe 2 S 3 , is very sensitive to temperature, pressure and compositional variations. This sensitivity has prevented its successful synthesis in a controlled laboratory environment. We report here the first successful synthesis of cubanite and its high-pressure Mössbauer spectroscopic and electrical properties up to 7 GPa. We also compare the Mössbauer spectroscopic and electrical resistivity results on our synthetic cubanite with the behavior of naturally occurring cuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…This short-lived phase was not structurally characterized, and moreover, these pH levels are inconsistent with predictions for pH levels of CI-chondrite parent-body fluids from mineral equilibria calculations (Dufresne and Anders 1962) and thermodynamic modeling of mineral assemblages (Zolensky et al 1989). More recent work has reported the synthesis of cubanite through radiative and microwave heating of copper, iron, and sulfur in evacuated silica tubes, a dry process (Pareek et al 2008;Chandra et al 2010Chandra et al , 2011. The experimentally formed CuFe 2 S 3 discussed herein is chemically and structurally consistent with orthorhombic cubanite, and is synthesized under aqueous conditions relevant to the CI-chondrite parent body at temperatures consistent with cubanite stability.…”
Section: Introductionmentioning
confidence: 90%
“…This short-lived phase was not structurally characterized, and moreover, these pH levels are inconsistent with predictions for pH levels of CI-chondrite parent-body fluids from mineral equilibria calculations (Dufresne and Anders 1962) and thermodynamic modeling of mineral assemblages (Zolensky et al 1989). More recent work has reported the synthesis of cubanite through radiative and microwave heating of copper, iron, and sulfur in evacuated silica tubes, a dry process (Pareek et al 2008;Chandra et al 2010Chandra et al , 2011. The experimentally formed CuFe 2 S 3 discussed herein is chemically and structurally consistent with orthorhombic cubanite, and is synthesized under aqueous conditions relevant to the CI-chondrite parent body at temperatures consistent with cubanite stability.…”
Section: Introductionmentioning
confidence: 90%
“…However, in the previous reports, it has been proven that the CuFe 2 S 3 will transform to a cubic form at high temperature [ 19–21 ]. The crystal structure of this cubic CuFe 2 S 3 is based on a cubic close-packed matrix of sulfur atoms, wherein the metal atoms are located in the tetrahedral interstices, furthermore, the ferrous, iron and cuprous ions are randomly distributed on these cation sites [ 15 , 20 ]. This special structure endows cubic CuFe 2 S 3 with unique photoelectricity and magnetic properties, which play a crucial role in biological application.…”
Section: Introductionmentioning
confidence: 99%
“…In this direction, synthesis of this rarely found mineral, cubanite (CuFe 2 S 3 ) was successfully attempted using conventional as well as microwave heating. The rapid microwave heating seems to be advantageous over conventional technique showing a characteristic peak of cubanite at d= 3.22 Å (Pareek et al 2008, Chandra et al 2010,2011. It is reported that synthesis of orthorhombic cubanite depends not only on the preparatory conditions (controlled heating and cooling rate) but also on compositional variation.…”
Section: Examples Of Microwave Synthesismentioning
confidence: 99%
“…Though x-ray diffraction pattern on conventionally synthesized sample does not indicate orthorhombic cubanite, Mössbauer spectroscopic studies confirm the presence of the phase through its sensitive parameters-magnetic hyperfine interaction and isomer shift. This is first ever study of successfully synthesized cubanite (Chandra et al 2010). The microwave dielectric heating effect originates from the natural ability of certain substances to efficiently absorb and to transform the electromagnetic energy into heat.…”
Section: Examples Of Microwave Synthesismentioning
confidence: 99%